Experimental and theoretical analysis of bismuth Co-doped erbium-based hydroxyapatites - Ali, Aenas Laith; Mahmood, Bahroz Kareem; Kareem, Rebaz Obaid; Ates, Tankut; Barzinjy, Azeez A.; Bulut, Niyazi; Kaygili, Omer (Springer, 2025)
This study explores the impact of bismuth (Bi) and erbium (Er) co-doping on the structural, morphological, and electronic properties of hydroxyapatites (HAp). Bi/Er co-doped HAp samples at varying concentrations were synthesized through a wet chemical process and characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). Additionally, density functional theory (DFT) was employed to analyze band structure (BS), energy gap (Eg), density of states (DOS), and linear attenuation coefficient (LAC). Results revealed a systematic decrease in the energy gap from 4.0340 eV to 3.9222 eV with increasing Bi content, highlighting a reduced band gap energy trend as the Bi and Er concentrations increase. Higher Bi concentration also influenced the DOS and BS, and reduced crystallite size (D) across samples. Among them, the 0.26Bi-0.39Er-HAp sample exhibited the lowest crystallinity (76.56%) and smallest crystallite size (27.84 nm). This study provides valuable insights into how co-doping affects HAp properties, with potential implications for biomedical and environmental applications.
Keywords: Hydroxyapatite; X-ray diffraction; Density functional theory; Energy gap; Co-doping